The regulation of the trade name in Peru: Lag and challenge - Schiantarelli Gonzalez, Juan Pablo (2015)
This paper analyzes the evolution of the regulation of trade names in the Andean Community and Peru, specifically in regard to its scope of protection from the provisions of article 8 of the Paris Convention (CUP). Also from certain rulings by IndecopI and the Court of Justice of the Andean Community, this paper contains a proposal of amendment to Decision 486 of the Andean Community and the legislative decree 1075 to update the regulation of trade names to modern times and ensure that the settlement of disputes involving said legal figure provide predictability and legal certainty.